RISK ANALYSIS AND PRIORITIZATION IN WATER SUPPLY NETWORK MAINTENANCE WORKS THROUGH THE FAILURE MODES AND EFFECTS ANALYSIS: OCCUPATIONAL SAFETY FMEA APPLICATION - Cavaignac, Andre Luis de Oliveira; Uchoa, Jhelison Gabriel Lima; dos Santos, Heyglon Fábio Oliveira (Brazilian Journal of Operations & Production Management, 2020)
Goal: In this work, the application of FMEA (failure mode and effects analysis) in the execution of maintenance of water network in a medium size city in the state of Maranhão was approached. FMEA (failure mode and effects analysis) with occupational safety approach is applied in the execution of water supply network maintenance in a medium size city in the state of Maranhão. This work shows that FMEA is an effective tool for risk prioritization in work process. The FMEA application with use of index reference table can become faster than application without reference table - and thus spread the tool for risk analysis. Design / Methodology / Approach: A photographic records was carried out in loco and the main risks to the workers were enumerated and based on the obtained data, a risk analysis was elaborated with the application of FMEA (Failure modes and effects analysis). Results: The maintenance services teams of the supply system are subject to a high risk of accidents caused mainly by the working conditions precariousness. It was observed that the services of manual excavations and the lack of use of PPE (helmet, gloves, pants suitable for flooded environments and etc.) have high risk index (RPN) and that the mismanagement added to the unsafe behavior were the main factors to accident occurrence in this type of work. Limitations of the investigation: The study studied the reality found in a medium-sized city with precarious working conditions. Further studies can compare the work reality of other teams in cities of different sizes, with better working conditions. Other limitation of this work is the impossibility of work situation improvement and posterior tool application – a study with this magnitude is non-trivial and needs future research. Practical implications: The great achievement of this work is to demonstrate that FMEA - a tool that is widely used in maintenance management and product engineering - is able to identify and prioritize risks based on its preliminary risk index obtained - contributing to reduce the difficulty of index choices previously cited in literature and disseminate the FMEA utilization for employee safety and occupational health. Such a tool has a great capacity for quantitative description of the risks, showing that the FMEA is very useful in the work safety sector for the organization of correction plans. Originality / Value: The difficulties of using the tool mentioned in the available literature were minimized with the use of the reference table, showing that the use of FMEA can become faster and thus spread the tool for risk analysis.